Inovasi Briket Durian untuk Pemberdayaan Ekonomi Kreatif Desa Blimbing Kabupaten Kediri dengan Berbasis Digital Marketing - Rahayuningtyas, Tri Esti; Himawan, Mahadika Pradipta; Negara, Wana Pramudyawardana Kusuma; Madany, Alek Zain; Kasanah, Uswatun (Universitas 45 Surabaya, 2025)
Blimbing Village, located in Mojo District, Kediri Regency, possesses superior horticultural potential in the form of durian. However, its utilization is still limited, which prevents it from generating a significant economic impact for the community. One of the main problems is the suboptimal management of the abundant durian peel waste after harvest, which leads to environmental issues. In reality, this waste has economic potential to be processed into environmentally friendly charcoal briquettes with broad market prospects. On the other hand, the limited use of digital technology prevents the marketing of local products from reaching a wider consumer base.This community service program aims to enhance the capacity of the Blimbing Village Youth Organization (Karang Taruna) in two main aspects: (1) production of charcoal briquettes based on durian peel waste, and (2) product marketing through a digital marketing strategy.The methods used include socialization, technical training on briquette production, entrepreneurship and digital marketing training (Instagram, TikTok, and Shopee), and implementation assistance in the field. The results of the activity show a significant increase in production skills, evidenced by the briquette quality being denser, more uniform, and having a longer burn time compared to wood charcoal. From a marketing perspective, the Youth Organization successfully created digital business accounts, uploaded educational content, and began marketing the product via Shopee.Overall, this program successfully integrated innovation based on local potential with a digital marketing strategy, thereby increasing the community's knowledge, skills, and entrepreneurial spirit.